Problems And Obsructions In Crime Scene And Evidence Preservation By Patrol Officers In Prachinburi Province - deepa, pitchayakorn; Suebpongsiri, sarit (Mahachula Academic Journal, 2025)
This mixed-methods research aimed to (1) study the perceptions of patrol police officers in Prachinburi Province regarding the effectiveness of their duties in crime scene and evidence protection, (2) examine the problems and obstacles encountered in performing those duties, and (3) assess the quality and appropriateness of operational guidelines for crime scene and evidence protection. The sample consisted of 182 patrol police officers who completed questionnaires, six experienced patrol officers (with over five years of service) who participated in in-depth interviews, and thirteen experts who evaluated the proposed development guidelines. The questionnaire sample was determined using Taro Yamane’s formula based on the total patrol police population in the province to ensure a sufficient and representative sample. The quantitative research instrument was a five-point Likert scale questionnaire with an Index of Item-Objective Congruence (IOC) of 1.00 and a Cronbach’s alpha coefficient of 0.80, indicating good reliability. Data were analyzed using descriptive statistics and content analysis. The findings revealed that patrol police officers recognized the importance of crime scene and evidence protection in supporting investigations, but still faced five major problems: insufficient equipment and vehicles, inadequate personnel, outdated and incomplete training, unclear laws and regulations, and a lack of cooperation from the public and relevant agencies. Experts strongly agreed with the proposed policy recommendations, which included providing equipment, increasing personnel, organizing modern training programs, revising laws and regulations, promoting inter-agency cooperation, and integrating technology to support operations. The study’s limitations include the sample size and geographic scope. It is therefore recommended that future studies be extended to other regions and include psychological factors and public perspectives to obtain more comprehensive data.